العلاقة بين الرطوبة والمادة العضوية في تربة السواحل الليبية: دراسة تطبيقية بمدينة الزاوية - رمضان العربي عبد الرحمن غومه (Surman Journal of Science and Technology, 2025)
The purpose of this research is to study the connection between soil moisture and organic matter content in coastal soils by performing an applied field study in Zawiya which serves as a western Libyan coastal city. The study selected three field sites which positioned themselves at different distances from the shoreline for surface soil collection at a defined time. The laboratory tested the samples to evaluate their moisture content through the gravimetric method and their organic matter content using the loss-on-ignition method. The research utilized descriptive analytical methods and Pearson’s correlation coefficient to evaluate the relationship between the two variables. Soil moisture levels exhibited a significant positive correlation with organic matter amounts and these levels increased as sampling sites moved closer to the coastal region. The physical and chemical traits of coastal soils are largely affected by climatic and geographical conditions. The research shows that moisture enhances organic matter decomposition processes as well as water retention capabilities of the soil through organic matter accumulation. The research demonstrates how moisture management needs collaboration with organic matter improvement for successful coastal soil enhancement programs. The authors suggest creating precise field-based soil databases to assist Libyan coastal area environmental and agricultural planning because of quickening climate change effects.